Cultural Interpretation of Emoji in Malaysian Context - Amalina, Intan Nadia; Azam, Yasir (European Publisher, 2019)
Emoji depicts real-world properties and infer their meaning through universal depictions. However, the interpretation of emoji are not necessarily understood collectively. One of the many factors influencing the interpretation of emoji is culture. The current study investigates the interpretation of emoji among three main cultures in Malaysia, namely the Malays, Chinese, and Indians. The respondents are digital natives from various parts across the country. The focus is on their interpretation of selected facial emoji namely the; sleeping face, tears of joy, loudly crying, blowing a kiss, and screaming in fear emoji. The analysis first identifies the interpretation of the emoji according to each culture, which is then followed by the analysis of differences in semantic misconstrual between the cultures. The results shows; (i) there are common interpretation shared among the three cultures for each emoji, highlighting the universal inherent meaning possessed by emoji, (ii) there are additional interpretations from each culture for each emoji, highlight the culturally specific interpretation for each emoji, and (iii) each culture have different degrees of variation in terms of interpretation for each emoji, highlighting the degree of potential misinterpretation among different cultures in intercultural communication. Overall, the study provides additional evidence of emoji interpretation being influenced by cultural idiosyncrasies, and understanding the differences can assist in smoother intercultural communication within a multicultural society such as in Malaysia.